Art as the absolute : art's relation to metaphysics in Kant, Fichte, Schelling, Hegel and Schopenhauer /: art's relation to metaphysics in Kant, Fichte, Schelling, Hegel and Schopenhauer. (2015 copyright 2015) - Unknown
No abstract available